Gastric ectopic pancreatic ductal adenocarcinoma coexisted with endometriosis mimick advanced disease: a case report and literature review - Wang, Jingwen; Zhu, Xia; Liu, Fei; Chen, Jiayan; Tang, Xi (Frontiers in Oncology, 2025)
Ectopic pancreas (EP) is most commonly located in the upper gastrointestinal tract, particularly in the stomach. Malignant transformation of EP is exceptionally rare, and due to its very low incidence, the response to drug therapy and overall prognosis remain poorly understood. This report presents a case of gastric ectopic pancreatic ductal adenocarcinoma. Unusually, the patient also had concurrent endometriosis, which caused the tumor to resemble advanced cancer on imaging. Although over 50 cases of malignant transformation of EP have been documented. Nevertheless, it has not been definitively established which drug therapeutic regimens is effective for this disease. This is the first to detail the tumor’s response to anti-tumor drug therapy. Pancreatic cancer is generally resistant to anti-tumor drugs. However, in this case, the tumor arising from EP regressed following treatment with immune checkpoint inhibitors (ICIs) combined with chemotherapy. This observation highlights differences in the biological behavior of these two tumor types.